Novel total synthesis of anserinone A and B. Issue 4 (16th February 2017) - Whisenant, Jonathan; Vinson, Daniel; Blanco, Michael; Hughes, Carson; David, Samuel
ABSTRACT: Anserinones A and B are natural products that have been shown to have potential anticancer, antifungal, and antibacterial properties. This work entails the novel synthesis of these natural products. GRAPHICAL ABSTRACT: